2 Hz EA Reduces Heroin Withdrawal-Induced Hyperalgesia and Heroin Relapse by Downregulating P2X3 Receptors in DRG Neurons. (26th December 2019) - Chen, Lin; Leng, Changlong; Gong, Xiaokang; Ma, Baomiao; Ru, Qin; Xiong, Qi; Zhou, Mei; Tian, Xiang; Yue, Kai; Li, Chaoying; Wu, Yuxiang
Abstract : Electroacupuncture (EA) has effective analgesic effects. Our previous study demonstrated that the upregulation of P2X3 receptors in the dorsal root ganglia (DRG) might participate in heroin withdrawal-induced hyperalgesia. The aim of this study is to further explore whether 2 Hz EA reduces heroin relapse associated with its analgesic effect and whether P2X3 receptors in the DRG are involved in this process. 2 Hz EA was adopted to treat the heroin SA rats in the present study. Heroin-seeking and pain sensitivity were evaluated. The expression of P2X3 receptors in the DRG was detected. Our results showed that compared with the control group, the reinstatement, thermal hyperalgesia, and mechanical allodynia of the heroin-addicted group were increased significantly. The expression of P2X3 receptors in the DRG was increased markedly. After being treated using 2 Hz EA, reinstatement was reduced, hyperalgesia was decreased, and the upregulated expression of P2X3 receptors in the DRG had decreased significantly compared to that in the heroin-addicted group. Consequently, our results indicated that 2 Hz EA was an effective method for treating heroin-induced hyperalgesia and helping prevent relapse, and the potential mechanism might be related to the downregulation of P2X3 receptor expression in the DRG.